2023
DOI: 10.1126/scisignal.abj8194
|View full text |Cite
|
Sign up to set email alerts
|

Serine-threonine phosphoregulation by PknB and Stp contributes to quiescence and antibiotic tolerance in Staphylococcus aureus

Abstract: Staphylococcus aureus can cause infections that are often chronic and difficult to treat, even when the bacteria are not antibiotic resistant because most antibiotics act only on metabolically active cells. Subpopulations of persister cells are metabolically quiescent, a state associated with delayed growth, reduced protein synthesis, and increased tolerance to antibiotics. Serine-threonine kinases and phosphatases similar to those found in eukaryotes can fine-tune essential bacterial cellular proc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 91 publications
0
12
0
Order By: Relevance
“…aureus, the overall number of phosphopeptides in the cell increased, especially in ribosomal proteins and elongation factors. This led to a decrease in the overall protein synthesis and an increase in antibiotic tolerance compared to the wild-type strain . Although that report cannot be directly compared to ours (they examined differentially expressed proteins, not genes, and they used deletion mutants, not an inhibitory molecule like loratadine), the results are intriguing because of the high degree of overlap in affected target genes/proteins.…”
Section: Discussionmentioning
confidence: 76%
“…aureus, the overall number of phosphopeptides in the cell increased, especially in ribosomal proteins and elongation factors. This led to a decrease in the overall protein synthesis and an increase in antibiotic tolerance compared to the wild-type strain . Although that report cannot be directly compared to ours (they examined differentially expressed proteins, not genes, and they used deletion mutants, not an inhibitory molecule like loratadine), the results are intriguing because of the high degree of overlap in affected target genes/proteins.…”
Section: Discussionmentioning
confidence: 76%
“… 122 Phosphatase Stp also impacted antibiotic resistance because Stp deletion strains are more susceptible to cell wall-acting antibiotics like tunicamycin, fosfomycin and β-lactam antibiotics, and Stp contributes to reduced susceptibility to vancomycin. 123 …”
Section: Resistance Mechanisms Of Mrsamentioning
confidence: 99%
“…This led to a decrease in overall protein synthesis and an increase in antibiotic tolerance compared to the wildtype strain. 38 While that report cannot be directly compared to ours (they examined differentially expressed proteins, not genes, and they used deletion mutants, not an inhibitory molecule), the results are intriguing because of the high degree of overlap in affected target genes/proteins. We found that loratadine reduced stp mRNA levels (Supporting Information Table S4), and in those cells, the downregulated genes were overrepresented with ribosomal genes.…”
Section: This Repression Of Translation Occurs Partly Via Phosphoryla...mentioning
confidence: 83%